Anti-VEGF therapy for proliferative diabetic retinopathy: translating research evidence into clinical practice - E.A. Abdulaeva; E.L. Minkhuzina; A.N. Kuskov (РМЖ "Клиническая офтальмология")
E.A. Abdulaeva1, E.L. Minkhuzina1,2, A.N. Kuskov2 1Kazan State Medical Academy — Branch of the Russian Medical Academy of Continuous Professional Education, Kazan, Russian Federation 2Prof. E.V. Adamyuk Republician Clinical Ophthalmological Hospital, Kazan, Russian Federation Diabetic retinopathy (DR) is a common microvascular complication of diabetes. As diabetes progresses, about 50% of patients with severe non-proliferative DR will develop proliferative DR (PDR) within one year. DR pathogenesis is mediated by alterations in many metabolic cascades, production of pro-inflammatory cytokines and growth factors, increased vascular leakage resulting from the loss of blood-retinal barrier integrity, and pathological neovascularization (which indicates increasing severity of DR). The introduction of anti-VEGF therapy has changed treatment paradigm for neovascularization as anti-VEGF agents target major pathophysiological mechanism of DR. Intensive studies on anti-VEGF therapy for PDR are now underway. This paper briefly reviews core studies on ranibizumab use in PDR and describes two case reports of PDR treatment with intravitreal injections of ranibizumab performed during one year according to prescribing information. Several clinical stud ies have demonstrated that anti-VEGF therapy is at least an alternative to panretinal photocoagulation in PDR. Our clinical observations confirm that ranibizumab is useful in routine clinical practice. Keywords: proliferative diabetic retinopathy, diabetic macular edema, vascular endothelial growth factor, anti-VEGF. For citation: Abdulaeva E.A., Minkhuzina E.L., Kuskov A.N. Anti-VEGF therapy for proliferative diabetic retinopathy: translating research evidence into clinical practice. Russian Journal of Clinical Ophthalmology. 2020;20(2):97–103. DOI: 10.32364/2311-7729-2020-20-2-97-103.